2004
DOI: 10.1097/00000441-200408000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Normal Exercise Blood Pressure Response in African-American Women with Parental History of Hypertension

Abstract: Background-Genetic and environmental hypotheses may explain why normotensive persons at high risk of developing hypertension often exhibit greater cardiovascular reactivity to stressors than those at low risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…40 The only study we know that analysed BP response to exercise in young normotensive women offspring of hypertensive parents failed to show any difference in BP response to exercise between positive and negative family history of hypertensive groups. 37 In contrast, although no significant difference was found between FH þ and FHÀ women, this study showed an increased diastolic BP response to exercise in FH þ þ compared with FHÀ women. Several methodological aspects may explain the differences between present and previous 37 studies.…”
Section: Pwvcontrasting
confidence: 79%
See 4 more Smart Citations
“…40 The only study we know that analysed BP response to exercise in young normotensive women offspring of hypertensive parents failed to show any difference in BP response to exercise between positive and negative family history of hypertensive groups. 37 In contrast, although no significant difference was found between FH þ and FHÀ women, this study showed an increased diastolic BP response to exercise in FH þ þ compared with FHÀ women. Several methodological aspects may explain the differences between present and previous 37 studies.…”
Section: Pwvcontrasting
confidence: 79%
“…37 And third, we separately analysed women with one and two hypertensive parents, and found higher BP response to exercise only in women with two hypertensive parents; on the other hand, previous study analysed women with one and two hypertensive parents as a single group. 37 The most likely explanation to the increased BP response to exercise commonly found among normotensive offspring of hypertensive parents appears to be a failure to reduce total peripheral resistance. 40 Although the precise mechanism involved in this failure is not clearly understood, an increased activation of sympathetic nervous system may be a mechanism contributing to the exaggerated exercise BP, and may probably have a key role in the pathogenesis of essential hypertension.…”
Section: Pwvmentioning
confidence: 85%
See 3 more Smart Citations